The Acehnese Language Use in South Aceh Regency: A Sociolinguistic Analysis - Zulkhairi, Zulkhairi; Zulhelmi, Anshar; Azhari, Azhari; Sumardi, Sumardi; Shaliha, Chairunnisa Ahsana Amalan (Buletin Al-Turas, 2024)
PurposeThis study aimed to find out how the Acehnese language is used by residents in the South Aceh Regency.MethodThis research used a qualitative approach with documentary studies, meta-ethnographic research, field studies, focus group discussions and in-depth interviews. The instruments used comprised data analysis forms, observation forms, focus group discussion guidelines, and in-depth interview guidelines. Data were analyzed qualitatively using the theory and concept of sociolinguistics Results/findingsThis study demonstrated that speakers of the Acehnese language in the South Aceh Regency came from distinct places than those in other Aceh regencies. The performance comprised performances in Acehnese language with and without acculturation of other languages, performances in Acehnese language with acculturation of the Aneuk Jamee language, performances in Acehnese language with acculturation of the Kluet language, performances in Acehnese language with acculturation of the Aneuk Jamee and Kluet languages, and performances in Acehnese language with acculturation of the Indonesian language. Conclusion The performance resulted from the presence of Acehnese speakers in multiethnic areas (Aneuk Jamee and Kluet tribes). Acehnese speakers have been encouraged to integrate with these tribes by their living conditions. Seeking a language that enables them to communicate with one another was the outward manifestation of these adaptation efforts.